Lipoid congenital adrenal hyperplasia by steroidogenic acute regulatory protein (STAR) gene mutation in an Italian infant: an uncommon cause of adrenal insufficiency - Carla Bizzarri (Italian Journal of Pediatrics, 2017)
Abstract Background Lipoid congenital adrenal hyperplasia (CAH) (OMIM n. 201710) is the most severe form of congenital adrenal hyperplasia. It is characterized by severe adrenal and gonadal steroidogenesis impairment due to a defect in the conversion of cholesterol to pregnenolone. Affected infants experience salt loss, but glucocorticoid and mineralocorticoid replacement therapy enables long-term survival. Classic lipoid congenital adrenal hyperplasia is relatively common in Japan and Korea but extremely rare in Caucasian populations. Case presentation A female infant of Italian origin came to our attention in late infancy with a clinical picture of acute adrenal insufficiency. The study of the STAR gene revealed two genomic variants c.562C > T and c.577C > T in compound heterozygosity. At the protein level, the two mutations determine the p.Arg188Cys variant (rs104894090) and the p.Arg193Ter variant (rs387907235), respectively. Sanger sequencing was used to confirm the identified variants and to perform familial study. The mother carried the p.Arg188Cys variant, while the father carried the p.Arg193Ter variant. Conclusion To our knowledge this is the second case of classic lipoid congenital adrenal hyperplasia reported in the Italian population. STAR mutations resulting in lipoid congenital adrenal hyperplasia should be considered all over the world in the differential diagnosis of newborn babies and infants with primary adrenal insufficiency.